2021
DOI: 10.1038/s41398-021-01302-0
|View full text |Cite
|
Sign up to set email alerts
|

“GrimAge,” an epigenetic predictor of mortality, is accelerated in major depressive disorder

Abstract: Major depressive disorder (MDD) is associated with premature mortality and is an independent risk factor for a broad range of diseases, especially those associated with aging, such as cardiovascular disease, diabetes, and Alzheimer’s disease. However, the pathophysiology underlying increased rates of somatic disease in MDD remains unknown. It has been proposed that MDD represents a state of accelerated cellular aging, and several measures of cellular aging have been developed in recent years. Among such metric… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
47
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 38 publications
5
47
0
1
Order By: Relevance
“…A similar situation may hold for depression and visual function, in the sense that depression can cause some changes in visual function (e.g., in contrast sensitivity, 55,56 although we did not observe that in our sample), and may impair visual function in general, in both clinical 21,57 and population 58 samples. Indeed, depression may be associated with a host of negative changes in physical health via accelerated aging effects 59 . In addition to possible effects on objective visual function, depression may also negatively bias self‐reports on a range of variables, including those we measured (e.g., perceived visual function, physical health and social support).…”
Section: Discussionmentioning
confidence: 99%
“…A similar situation may hold for depression and visual function, in the sense that depression can cause some changes in visual function (e.g., in contrast sensitivity, 55,56 although we did not observe that in our sample), and may impair visual function in general, in both clinical 21,57 and population 58 samples. Indeed, depression may be associated with a host of negative changes in physical health via accelerated aging effects 59 . In addition to possible effects on objective visual function, depression may also negatively bias self‐reports on a range of variables, including those we measured (e.g., perceived visual function, physical health and social support).…”
Section: Discussionmentioning
confidence: 99%
“…Major depressive disorder (MDD), one of the most common serious psychiatric disorders worldwide, is associated with increased risks of many biological and physiological pathologies such as dementia/cognitive decline ( Byers and Yaffe, 2011 ; Holmquist et al, 2020 ), cardiovascular disease ( Gan et al, 2014 ), and osteoporosis ( Cizza et al, 2009 ) which occur in the process of normal aging. Accordingly, there are growing evidences suggesting that MDD leads to an accelerated biological aging as revealed by biochemical ( Wolkowitz et al, 2011 ; Levada and Troyan, 2020 ), genetic ( Simon et al, 2006 ; Protsenko et al, 2021 ), and neuroimaging ( Sacchet et al, 2017 ; Cheng et al, 2020 ; Dunlop et al, 2021 ) characteristics. For instance, it was found that MDD patients are significantly older (with a median gap of 2 years) than their chronological age based on predictable age-related patterns of DNA methylation ( Protsenko et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, there are growing evidences suggesting that MDD leads to an accelerated biological aging as revealed by biochemical ( Wolkowitz et al, 2011 ; Levada and Troyan, 2020 ), genetic ( Simon et al, 2006 ; Protsenko et al, 2021 ), and neuroimaging ( Sacchet et al, 2017 ; Cheng et al, 2020 ; Dunlop et al, 2021 ) characteristics. For instance, it was found that MDD patients are significantly older (with a median gap of 2 years) than their chronological age based on predictable age-related patterns of DNA methylation ( Protsenko et al, 2021 ). Structural neuroimaging studies have also reported that age-related reductions in the brain cortical thickness ( Cheng et al, 2020 ) and putamen volumes ( Sacchet et al, 2017 ) are accelerated in MDD.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, epigenetic age acceleration or faster "epigenetic clock" has been linked to health decline including higher mortality risk [12] and faster cognitive decline [7,9,13,14]. However, few epidemiological studies have directly linked epigenetic clocks or DNAm to MDD [15][16][17] and only two have directly or indirectly examined its association with elevated depressive symptoms [5,6].…”
Section: Introductionmentioning
confidence: 99%